Rare case of rhinosporidiosis: a case report from Jammu - M. K., Vinod; Kaur, Amanjoth; Devgan, Kamal; Singh, Jagdeepak (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Rhinosporidiosis is an uncommon chronic granulomatous infection that affects the nasal mucosa, ocular conjunctiva and other mucosa. The disease is most common in southern India and Sri Lanka. It is rare in northern states of India. The present report of rhinopsoridiosis constitutes the very few reported cases of rhinosporidiosis in a resident of Jammu and Kashmir state of India, who has no history of travel to any of the areas endemic for the disease in India or elsewhere.